Unique fatty acid desaturase capacities uncovered in Hediste diversicolor illustrate the roles of aquatic invertebrates in trophic upgrading - Kabeya, Naoki; Gür, İbrahim; Oboh, Angela; Ove Evjemo, Jan; Malzahn, Arne M.; Hontoria, Francisco; Navarro, Juan Carlos; Monroig, Óscar (Royal Society (Great Britain), 2020)
Omega-3 (ω3 or n-3) long-chain polyunsaturated fatty acids (PUFA) including eicosapentaenoic acid and docosahexaenoic acid (DHA), play physiologically important roles in vertebrates. These compounds have long been believed to be originated almost exclusively from aquatic (mostly marine) single-cell organisms. Yet, a recent study has discovered that many invertebrates possess a type of enzymes called methyl-end desaturases (ωx) that enables them to endogenously produce n-3 long-chain PUFA and could make a significant contribution to production of these compounds in the marine environment. Polychaetes are major components of benthic fauna and thus important to maintain a robust food web as a recycler of organic matter and a prey item for higher trophic level species like fish. In the present study, we investigated the ωx enzymes from the common ragworm Hediste diversicolor, a common inhabitant in sedimentary littoral ecosystems of the North Atlantic. Functional assays of the H. diversicolor ωx demonstrated unique desaturation capacities. An ω3 desaturase mediated the conversion of n-6 fatty acid substrates into their corresponding n-3 products including DHA. A further enzyme possessed unique regioselectivities combining both ω6 and ω3 desaturase activities. These results illustrate that the long-chain PUFA biosynthetic enzymatic machinery of aquatic invertebrates such as polychaetes is highly diverse and clarify that invertebrates can be major contributors to fatty acid trophic upgrading in aquatic food webs. This study was funded through the project IMPROMEGA of the Ministry of Science, Innovation and Universities, Spanish Government (grant no. RTI2018-095119-B-I00, MCIU/AEI/FEDER, UE). N.K. was funded by the Japan Society for the Promotion of Science through Grant-in-Aid for JSPS Fellows (grant no. 16J06812). İ.G. received funding from the Ministry of National Education, Republic of Turkey. A.O. was funded by the Commonwealth Scholarship Commission (grant no. NGCS-2014-438) in the UK. A.M.M. acknowledges the ...